AKSESIBILITAS ANAK BERKEBUTUHAN KHUSUS DI ERA PENDIDIKAN 4.0 - Melda Rumia Rosmery Simorangkir; Jitu Halomoan Lumbantoruan (Jurnal Dinamika Pendidikan, 2021)
his research was conducted to measure the extent to which teachers understand education in the 4.0 era for special needs and disabilities and how the efforts of inclusive schools in providing accessibility to education era 4.0 for special needs and disabilities. This research was conducted using qualitative methods with a descriptive approach. Primary data sources include observation, observation, interview, documentation, and triangulation. The informants of this study were teachers and educators and education staff in four inclusive public elementary schools in Bekasi. From this study, it was found that not all teachers understood education with special needs in the education era 4.0. Self-development training for teachers is needed so that they are ready to face education in the 4.0 era